Po naszymu o pasjach. Gwara zaolziańska w mediach społecznościowych - Bogoczová, Irena; Bortliczek, Małgorzata (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2022)
<span dir="ltr" style="left: calc(var(–scale-factor)*74.66px); top: calc(var(–scale-factor)*300.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.966357);" role="presentation">The article is a <span dir="ltr" style="left: calc(var(–scale-factor)*133.68px); top: calc(var(–scale-factor)*300.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.03723);" role="presentation">contribution <span dir="ltr" style="left: calc(var(–scale-factor)*186.24px); top: calc(var(–scale-factor)*300.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02185);" role="presentation">to <span dir="ltr" style="left: calc(var(–scale-factor)*196.04px); top: calc(var(–scale-factor)*300.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.998001);" role="presentation">the research on <span dir="ltr" style="left: calc(var(–scale-factor)*258.31px); top: calc(var(–scale-factor)*300.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.988639);" role="presentation">the linguistic situation <span dir="ltr" style="left: calc(var(–scale-factor)*348.05px); top: calc(var(–scale-factor)*300.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.986864);" role="presentation">of the Czech part <span dir="ltr" style="left: calc(var(–scale-factor)*75.25px); top: calc(var(–scale-factor)*314.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.977531);" role="presentation">of Těšín Silesia (<span dir="ltr" style="left: calc(var(–scale-factor)*141.76px); top: calc(var(–scale-factor)*314.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.971324);" role="presentation">Zaolzie <span dir="ltr" style="left: calc(var(–scale-factor)*173.61px); top: calc(var(–scale-factor)*314.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01313);" role="presentation">in Polish). Having written on <span dir="ltr" style="left: calc(var(–scale-factor)*294.25px); top: calc(var(–scale-factor)*314.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02557);" role="presentation">the topic in the past, this time <span dir="ltr" style="left: calc(var(–scale-factor)*75.21px); top: calc(var(–scale-factor)*328.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.03819);" role="presentation">the authors direct their attention <span dir="ltr" style="left: calc(var(–scale-factor)*210.70px); top: calc(var(–scale-factor)*328.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02185);" role="presentation">to <span dir="ltr" style="left: calc(var(–scale-factor)*221.50px); top: calc(var(–scale-factor)*328.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01928);" role="presentation">the Jablunkov part of the region <span dir="ltr" style="left: calc(var(–scale-factor)*354.30px); top: calc(var(–scale-factor)*328.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.05057);" role="presentation">and to a <span dir="ltr" style="left: calc(var(–scale-factor)*390.41px); top: calc(var(–scale-factor)*328.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.0012);" role="presentation">mixed <span dir="ltr" style="left: calc(var(–scale-factor)*75.17px); top: calc(var(–scale-factor)*342.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.979575);" role="presentation">language: the so-called <span dir="ltr" style="left: calc(var(–scale-factor)*167.31px); top: calc(var(–scale-factor)*342.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.948231);" role="presentation">po <span dir="ltr" style="left: calc(var(–scale-factor)*178.60px); top: calc(var(–scale-factor)*342.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00144);" role="presentation">naszymu<span dir="ltr" style="left: calc(var(–scale-factor)*214.20px); top: calc(var(–scale-factor)*342.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.984568);" role="presentation">. In the introduction, they reflect on <span dir="ltr" style="left: calc(var(–scale-factor)*356.00px); top: calc(var(–scale-factor)*342.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.0035);" role="presentation">what functions a <span dir="ltr" style="left: calc(var(–scale-factor)*82.81px); top: calc(var(–scale-factor)*356.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02381);" role="presentation">dialect can fulfil today, most of which are evident in the authentic linguistic mate<span dir="ltr" style="left: calc(var(–scale-factor)*75.16px); top: calc(var(–scale-factor)*370.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01239);" role="presentation">rial presented which comes from three extensive interviews that have then been pub<span dir="ltr" style="left: calc(var(–scale-factor)*75.17px); top: calc(var(–scale-factor)*384.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.999313);" role="presentation">lished online. The speech of the dialect’s <span dir="ltr" style="left: calc(var(–scale-factor)*240.78px); top: calc(var(–scale-factor)*384.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.992585);" role="presentation">speakers differs, revealing the general focus <span dir="ltr" style="left: calc(var(–scale-factor)*75.25px); top: calc(var(–scale-factor)*398.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.990523);" role="presentation">of the speaker on a <span dir="ltr" style="left: calc(var(–scale-factor)*151.86px); top: calc(var(–scale-factor)*398.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.988016);" role="presentation">particular ethnic language: Polish, Czech or Slovak. The discovery <span dir="ltr" style="left: calc(var(–scale-factor)*75.25px); top: calc(var(–scale-factor)*412.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.99982);" role="presentation">of these foreign elements is possible due to <span dir="ltr" style="left: calc(var(–scale-factor)*250.37px); top: calc(var(–scale-factor)*412.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.0155);" role="presentation">the phonetic transcription, which reveals <span dir="ltr" style="left: calc(var(–scale-factor)*75.17px); top: calc(var(–scale-factor)*426.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.994234);" role="presentation">lexical, morphological and phonetic transfers in the texts. The purpose of the analysis <span dir="ltr" style="left: calc(var(–scale-factor)*75.18px); top: calc(var(–scale-factor)*440.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.974041);" role="presentation">is to <span dir="ltr" style="left: calc(var(–scale-factor)*93.94px); top: calc(var(–scale-factor)*440.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00392);" role="presentation">point out the differences in the <span dir="ltr" style="left: calc(var(–scale-factor)*218.98px); top: calc(var(–scale-factor)*440.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.949);" role="presentation">po <span dir="ltr" style="left: calc(var(–scale-factor)*230.72px); top: calc(var(–scale-factor)*440.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00222);" role="presentation">naszymu <span dir="ltr" style="left: calc(var(–scale-factor)*268.61px); top: calc(var(–scale-factor)*440.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.98787);" role="presentation">mixed language code with a <span dir="ltr" style="left: calc(var(–scale-factor)*381.71px); top: calc(var(–scale-factor)*440.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.993869);" role="presentation">different <span dir="ltr" style="left: calc(var(–scale-factor)*75.16px); top: calc(var(–scale-factor)*454.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00934);" role="presentation">rate <span dir="ltr" style="left: calc(var(–scale-factor)*92.56px); top: calc(var(–scale-factor)*454.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.975917);" role="presentation">of Polish, Czech or Slovak elements.